1999
DOI: 10.1080/0158791990200109
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of business college faculty and administrators toward distance education: a national survey

Abstract: Educators' attitudes towards distance education are known to be influenced by many factors. This study incorporated survey data that measured business educators' attitudes toward distance education at both the baccalaureate and masters levels of instruction. Two simultaneous equations models were developed that described the relationship between the respondents' attitudes and other factors relevant to their receptivity and support of distance education. Key influential factors were found to be the experience o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In addition, many studies have attempted to discover the relationship between faculty attitudes towards teaching online courses and corresponding factors, such as institutional policy, administrative expectations, demands from the community, release of time and monetary rewards, etc. (Freberg et al , 1995; Nasser and Abouchedid, 2002; Ross and Klug, 1999; Siaciwena, 1989; Taylor and White, 1991; Wilson, 2001; Wolcott and Betts, 1999). Bates (1997) suggests it is strategically important to make sure that faculty participation in using technologies for teaching is encouraged and supported by all means.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, many studies have attempted to discover the relationship between faculty attitudes towards teaching online courses and corresponding factors, such as institutional policy, administrative expectations, demands from the community, release of time and monetary rewards, etc. (Freberg et al , 1995; Nasser and Abouchedid, 2002; Ross and Klug, 1999; Siaciwena, 1989; Taylor and White, 1991; Wilson, 2001; Wolcott and Betts, 1999). Bates (1997) suggests it is strategically important to make sure that faculty participation in using technologies for teaching is encouraged and supported by all means.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ross & Klug (1999), Rockwell et al (2000) and Butner, Smith, & Murray, (1999) all found institutional type to be an issue in measuring faculty attitudes, and this investigation could further describe that phenomenon.…”
Section: Alpha 8898mentioning
confidence: 68%
“…The final models for both academic levels showed several similarities but also a few significant differences. Ross and Klug (1999) found that at both the baccalaureate and the master's level, business school faculty and administrators who believed distance education was a good fit with their personal and institutional goals showed a high degree of receptivity to distance education. Individuals who perceived more difficulties with distance education were less receptive.…”
Section: Faculty and Administrator Attitudesmentioning
confidence: 99%
See 2 more Smart Citations